2013
DOI: 10.1074/jbc.m113.452458
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pancreatic Cancer-derived Exosomes in Salivary Biomarker Development

Abstract: Background: Salivary biomarkers for systemic diseases have been undermined due to lack of mechanistic and biological rationale. Results: Suppression of exosome biogenesis leads to ablation of salivary biomarkers. Conclusion: Tumor-derived exosomes provide a mechanism for discriminatory biomarkers in saliva. Significance: Tumor-derived exosomes provide the scientific rationale that connects pancreatic tumors and the oral cavity leading to salivary biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 29 publications
5
166
0
4
Order By: Relevance
“…Moreover, we did not observe differences in the total protein concentration or ␣-amylase activity between wild-type and PAP Ϫ/Ϫ mice. However, we cannot disregard potential differences in the particular composition of the saliva, considering that systemic diseases can induce alterations in the profile of components that are secreted into the saliva (15,30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not observe differences in the total protein concentration or ␣-amylase activity between wild-type and PAP Ϫ/Ϫ mice. However, we cannot disregard potential differences in the particular composition of the saliva, considering that systemic diseases can induce alterations in the profile of components that are secreted into the saliva (15,30).…”
Section: Discussionmentioning
confidence: 99%
“…47 Using a rodent pancreatic cancer model, we have demonstrated that tumor-specific mRNA markers are shed from the pancreatic tumor cells, packaged in exosome and shuttled to salivary gland. 48 …”
Section: Future Perspectivesmentioning
confidence: 99%
“…Salivary miRNA biomarkers have recently become an emerging field for monitoring oral diseases and systemic diseases Lau et al, 2013;Yoshizawa et al, 2013). In carcinogenesis, overexpression of certain miRNAs could result in downregulation of tumor suppressor genes, while underexpression of certain miRNAs could cause oncogene upregulation (Chen, 2005).…”
Section: Introductionmentioning
confidence: 99%